Increasing the Capacity of Teachers and Students in Understanding the Concept of Environmental Awareness of Honey Bee Cultivation - Papilaya, Pamela Mercy; Lamerkabel, Jacobus SA; Tuapattinaya, Prelly MJ (Pascasarjana Universitas Mataram, 2024)
Bees are honey-producing insects from the genus apis. In addition to honey, bees also produce pollen, royal jelly, propolis, beeswax and bee venom. Honey products that are widely found in Indonesia come from local honey bees, superior bees, wild bees, and lanceng bees. The high demand has driven up the price of honey bee products. Propolis has various health benefits such as containing high antioxidants and phenols, so it has the potential to cure various diseases such as toothache, influenza, diabetes mellitus, tuberculosis, and others. The purpose of this community service is to provide assistance to students regarding environmental awareness of honey bee cultivation at the Pattimura University Laboratory Middle School, Ambon and to increase the capacity of teachers in understanding the concept of environmental awareness of honey bee cultivation. The steps taken for learning honey bee cultivation use Project based learning (PjBL).